Unhealthy lifestyle behaviors, overweight, and obesity among childhood cancer survivors in the Netherlands: A DCCSS LATER study - Bouwman, Eline; Penson, Adriaan; Valk, Maud; Oever, Selina R.; Pal, Helena J. H.; Dulmen‐den Broeder, Eline; Blijlevens, Nicole M. A.; Bresters, Dorine; Feijen, Elizabeth A. M.; Heuvel‐Eibrink, Marry M.; Heiden‐van der Loo, Margriet; Michel, Gisela; et al. (Cancer, 2024)
Background The objective of this study was to examine the prevalence of unhealthy lifestyle behaviors, overweight, and obesity in Dutch childhood cancer survivors (CCSs) compared with sibling controls and the Dutch general population. Other aims were to assess associated factors of unhealthy lifestyle behaviors, overweight, and obesity and to identify subgroups of CCSs at risk for these unhealthy statuses. Methods The authors included 2253 CCSs and 906 siblings from the Dutch Childhood Cancer Survivor Study‐Late Effects After Childhood Cancer cohort, part 1, and added data from the Dutch general population. Questionnaire data were collected on overweight and obesity (body mass index >25.0 kg/m2), meeting physical activity guidelines (>150 minutes per week of moderate or vigorous exercises), excessive alcohol consumption (>14 and >21 alcoholic consumptions per week for women and men, respectively), daily smoking, and monthly drug use. Multivariable logistic regression analyses and two‐step cluster analyses were performed to examine sociodemographic‐related, health‐related, cancer‐related, and treatment‐related associated factors of unhealthy lifestyle behaviors and to identify subgroups of CCSs at risk for multiple unhealthy behaviors. Results CCSs more often did not meet physical activity guidelines than their siblings (30.0% vs. 19.3%; p < .001). Married as marital status, lower education level, nonstudent status, and comorbidities were common associated factors for a body mass index ≥25.0 kg/m2 and insufficient physical activity, whereas male sex and lower education were shared associated factors for excessive alcohol consumption, daily smoking, and monthly drug use. A subgroup of CCSs was identified as excessive alcohol consumers, daily smokers, and monthly drug users. Conclusions The current results emphasize the factors associated with unhealthy behaviors and the potential identification of CCSs who exhibit multiple unhealthy lifestyle behaviors. The results of this study indicate a higher prevalence of physical inactivity in childhood cancer survivors compared with sibling controls and the Dutch population, emphasizing the necessity for personalized health behavior interventions in childhood cancer survivors. These findings can be used in clinical practice to create awareness and to identify subgroups of childhood cancer survivors who need special attention regarding health behaviors.